Synthesis, characterization and catalytic study of functionalized polymer supported palladium(II) hydrazone complexes containing electron donating group as catalysts in heck reaction / Najwa Asilah M Shamsuddin - M Shamsuddin, Najwa Asilah (2023)
Heck reaction was discovered as one of the cross-coupling reactions where the coupling occurs between aryl halides and alkenes that using palladium as catalyst. Immobilization of catalysts on insoluble supports which is chloromethylated polystyrene or Merrifield resin have been expected as best substitutes to soluble polymer supports due to inert, non-toxic, and non-volatile characteristics. Thus, this study reports on the synthesis and characterization of functionalized polystyrene-supported palladium(II)-hydrazone complexes containing electron donating group (-OH and -CH3) and their catalytic behaviour for Heck reaction. The first step of synthesis began with aldehyde functionalization of chloromethylated polystyrene to form PS-CHO.